INTEGRASI GAYA KEPEMIMPINAN, REWARD, PUNISHMENT, DAN WORK LIFE BALANCE TERHADAP MOTIVASI KERJA - Muhammad Fadil Laela Arbi; Yudhistira Pradhipta Aryoko; Fatmah Bagis; Arini Hidayah (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to try to test and indicate the integration of leadership style, reward, punishment, and work life balance in increasing nurses' work motivation at Banyumas Regional General Hospital. This research is quantitative. The population includes all nurses at Banyumas Regional General Hospital. The Slovin formula was used to calculate a sample of 154 nurses at Banyumas Regional General Hospital. SmartPLS version 3.0 was used to analyze the validity, reliability, and hypothesis testing of the data. This research uses a survey model using a questionnaire distributed to nurses. The results showed that leadership style, reward, and work-life balance are statistically significant on work motivation, while punishment is not statistically significant on work motivation of nurses at Banyumas Regional General Hospital. This finding shows that the punishment system is more likely to increase dissatisfaction related to hygienic factors, but is not able to increase overall work motivation.